Clodronate-liposomes aggravate irradiation-induced myelosuppression by promoting myeloid differentiation. (1st February 2021) - Ju, Wen; Lu, Wenyi; Bao, Yurong; Sun, Tiantian; Adzraku, Seyram Yao; Fu, Chunling; Qi, Kunming; Zhang, Xi; Li, Zhenyu; Xu, Kailin; Qiao, Jianlin; Zeng, Lingyu
Abstract: Purpose: Clodronate-liposomes (Clod-Lip) is an effective candidate drug for treating chronic myelomonocytic leukemia, autoimmune hemolytic anemia and immune thrombocytopenic purpura in mice experiments. But its role in hematopoietic recovery after acute myelosuppression is still unknown. We aim to explore the function and underlining mechanisms of Clod-Lip on hematopoietic reconstitution after sublethal dose irradiation in mice. Materials and methods: Mice at 8-10 weeks received a total-body sublethal dose γ-irradiation (TBI) and injected with Clod-Lip or PBS-Liposomes (PBS-Lip) every 4 days after TBI. The survival rate of each group was recorded. Flow cytometry was used to analyze changes in hematopoietic stem cells and their progenies in bone marrow. ELISA and RT-qPCR were used for the analysis of hematopoietic regulatory factors. Regarding IL-1β inhibition, 25 mg/kg diacerein or an equal volume of DMSO was intraperitoneally injected into mice every day after TBI. Results: In sublethal dose-irradiated mice, Clod-Lip reduced the survival rate, the total number of bone marrow and hematopoietic stem cells, delayed peripheral blood recovery of red blood cells and platelets. However, it could increase the number of CMP, MEP and myeloid cells, which suggested that Clod-Lip could induce HSC to myeloid differentiation in vivo. We further verified that Clod-Lip may induce myeloid differentiation by bone marrow microenvironmental factor IL-1β. Conclusions: In summary, this study suggested that Clod-Lip may aggravate inhibitor effect of hematopoietic function and promote myeloid differentiation in myelosuppression mice model.